Interferência no sistema WCDMA - Vieira, Carla Matheus Moreira (2010)
Due to modifications in the user profile, which shows an increasing demand for new data services, high transmission rates, video downloads, interactive multimedia and highquality images, a very rapid growth in 3G networks has been observed when compared to other cellular systems technologies. This dissertation deals with the performance of WCDMA systems in interference environments. Because WCDMA systems are limited to interference, a study for evaluating the influence of this parameter in network performance is important and necessary. This work presents a study covering both internal interference and the interference due to adjacent channel in the case of operators offering 3G services in the same geographical area. Initially, the characteristics of WCDMA systems and the radio resources management mechanisms directly linked to the interference problem are introduced. Subsequently, comments on the interference mechanisms, including the mathematical formulation are presented. A detailed description of the simulation methodology concludes the necessary information for the application of the open software NPSW used in this work. Numerical results covering different scenarios are then evaluated and discussed. Based on the analysis of these results, it was possible to list some planning and optimizing recommendations for WCDMA networks in order to avoid network performance degradation due to interference.